Evaluation of toxic effects of petroleum hydrocarbon on Mytilus coruscus under different salinity based on an integrated biomarker response index. Issue 1 (31st December 2022) - Li, Lei; Wang, Cuihua; Li, Ziniu; Xv, Guodong; Tang, Baojun; Jiang, Mei
ABSTRACT: An oxidative stress experiment of crude oil in Pinghu on Mytilus coruscus under different salinities (10, 15 and 20) for 15 days was carried out in this study. Oxidative stress of oil pollutants in digestive glands was measured by several typical biomarkers, the levels of ethoxyresourufin-O-deethylase (EROD) activities and aryl hydrocarbon hydroxylase (AHH) activities, CYP1A1mRNA content and DNA damage degree. The integrated biomarker response index (IBR) was introduced in for the quantitative evaluation of the responses of M. cephalus to the toxic effects of crude oil in Pinghu under different salinities. The results showed that the different salinities of crude oil in Pinghu can induce toxic effects on the digestive glands of M. coruscus to different extents, and the order of the degrees of toxicity, which were higher than those of the control groups, was 20 salinity > 15 salinity > 10 salinity. .